Ultrasound and magnetic resonance imaging of cyclic arginine glycine aspartic acid-gadopentetic acid-polylactic acid in human breast cancer by targeting αvβ3 in xenograft-bearing nude mice. Issue 3 (1st March 2022) - Fu, Danhui; Huang, Xiangyang; Lv, Zheng; Zhang, Yupeng; Chen, Miao; Zhang, Wei; Su, Danke
ABSTRACT: Effective early detection shows the potential to reduce breast cancer mortality. This study aimed to establish a targeted contrast agent for Magnetic Resonance Imaging (MRI)/ultrasound dual-modality molecular radiography for breast cancer. The cyclic arginine-glycine-aspartate-gadopentetic acid-polylactic acid (cRGD and Gd-DTPA) coated by multi-functional blank poly (lactic-co-glycolic acid) (PLGA) nanoparticles) was successfully constructed by chemical synthesis method with high stability. The safety of cRGD-Gd-DTPA-PLGA was demonstrated in vitro and in vivo, and their affinity to breast cancer cells was revealed. Moreover, MRI/ultrasound dual-modality molecular radiography in vitro showed that as the concentration of contrast agent increased, the echo enhancement and signal intensity of MRI imaging were also elevated. The mouse models of human breast cancer also indicated significant target enhancements of cRGD-Gd-DTPA-PLGA magnetic nanoparticles in the mouse tumor. Thus, cRGD-Gd-DTPA-PLGA magnetic nanoparticles were suggested as qualified MRI/ultrasound dual-modality molecular radiography contrast agent. We further explored the targeting mechanism of cRGD-Gd-DTPA-PLGA in breast cancer. The results showed that αvβ3 was highly expressed in breast cancer tissues, and cRGD-Gd-DTPA-PLGA used for MRI/ultrasound dual-modality molecular radiography by targeting αvβ3. Additionally, we found that the signal-to-noise ratio of MRI was positively correlated with microvessel density (MVD). The cRGD-Gd-DTPA-PLGA dynamicly and quantitatively monitored breast cancer by monitoring the state of neovascularization. In conclusion, in the present study, we successfully constructed the cRGD-Gd-DTPA-PLGA magnetic nanoparticles for MRI/ultrasound dual-modality molecular radiography. The cRGD-Gd-DTPA-PLGA showed potential in early detection and diagnosis of metastasis, and dynamic evaluation of the efficacy of molecular targeted therapy of integrin αvβ3. Graphical abstract: uf0001